2010
DOI: 10.1111/j.2042-3292.2010.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of 14 cases of hypertrophic osteopathy (Marie's disease) in horses in the Republic of Ireland

Abstract: Summary There are few reports describing hypertrophic osteopathy (HO) in horses and no reports describing this in the Irish equine population. This case series outlines the clinical, radiological and pathological features of HO in horses in Ireland and compares and contrasts the findings to previous reports. Overall, the prevalence of HO in Irish horses was found to be low with clinical signs similar to previous reports. Diagnosis of the primary lesion was low, largely due to the limited diagnostic evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
2
11
1
1
Order By: Relevance
“…The diagnosis of HO (Marie's disease) was made from the clinical signs, radiographic features of the long bones, presence of a large intra‐abdominal mass concurrently and response to treatment. Hypertrophic osteopathy is a poorly understood, rare condition characterised by symmetrical proliferation of connective tissue and subperiosteal bone along the diaphysis of the long bones (Mair and Tucker 2004; Enright et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis of HO (Marie's disease) was made from the clinical signs, radiographic features of the long bones, presence of a large intra‐abdominal mass concurrently and response to treatment. Hypertrophic osteopathy is a poorly understood, rare condition characterised by symmetrical proliferation of connective tissue and subperiosteal bone along the diaphysis of the long bones (Mair and Tucker 2004; Enright et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
“…2009) and macropods (Wayne and Nicholson 1999). In the human literature, the condition is referred to as hypertrophic osteoarthropathy (HOA) due to associated arthritis (Nguyen and Hojjati 2011); however, in animal species direct association with the joints does not appear to occur (Enright et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A última denominação é usada para designar a doença em humanos devido ao frequente envolvimento articular, o que não ocorre nos cães, nos quais a lesão se concentra nos ossos (Goldstraw & Walbaum 1976, Liptak et al 2004. Além de humanos e cães, espécies nas quais a doença ocorre com maior frequência, OH também tem sido descrita em gatos (Grierson et al 2003, Johnson & Lenz 2011, equinos (Mair et al 1996, Heinola et al 2001, Enright et al 2011, bovinos (Martin et al 1971), veados (Ferguson et al 2008), visons (Wilton & Graesser 1967), primatas e leões (Brodey 1971).…”
Section: Introductionunclassified
“…Chaffin et al (1990) reported HO regression after treatment of an intrathoracic abscess in a horse. Enright et al (2011) described HO regression in two animals treated with nonsteroidal antiinflammatories (NSAIDs) and corticosteroids. The horses had HO secondary to splenomegaly and inflammatory airway disease, respectively.…”
Section: Case Reportmentioning
confidence: 99%